Identifying Self-Reported Strategies to Acquire Proficiency in Laparoscopic Surgery Training Simulation - Cao, Yuyuan; Chi, Ethan; Chen, Yufei; Wu, Jiaqi; Oh, Jinwoo; Deng, Shiyu; Lau, Nathan (Proceedings of the International Symposium of Human Factors and Ergonomics in Healthcare, 2025)
Self-reported challenges and strategies can inform effective and personalized training program in acquiring motor-control skills for laparoscopic surgery that accounts for over 15 million procedures annually. This article presents an interview study of thirteen participants who completed a longitudinal experiment to identify the challenges encountered and strategies used by individuals self-training the peg transfer task in the Fundamental of Laparoscopic Surgery. Thematic analysis revealed that participants were challenged with high cognitive load and instrument handling to improve performance continually and derived improvement strategies through task understanding and goal settings to achieve proficiency.